2014
DOI: 10.4067/s0717-95022014000100010
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Ponticulus Posticus in Lateral Cephalometric Radiography of Peruvian Patients

Abstract: SUMMARY:The Ponticulus posticus is an anomalous ossification of unknown origin that arches backward from the superior articular process to the posterior arch of the Atlas vertebra, it can be complete or partial and houses vascular and nervous elements; it is diagnosed by lateral cervical radiography, cephalometric radiography or CT scans. The purpose for the present study was to determine the frequency of partial and complete Ponticulus posticus in lateral cephalometric radiography of Peruvian patients and ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 16 publications
0
18
0
2
Order By: Relevance
“…The criteria for determining the PP, STB and CLEN were the same utilized in previous publications (Pérez et al, 2013(Pérez et al, , 2014: with the samples of the studies of PP, STB and CLEN realized in non-cleft Peruvian patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The criteria for determining the PP, STB and CLEN were the same utilized in previous publications (Pérez et al, 2013(Pérez et al, , 2014: with the samples of the studies of PP, STB and CLEN realized in non-cleft Peruvian patients.…”
Section: Introductionmentioning
confidence: 99%
“…The frequencies of Ponticulus Posticus (complete and partial) in the Atlas vertebrae; the Sella Turcica Bridge and the Clinoid Enlargement in Peruvians were determined in two distinct studies (Pérez et al, 2013(Pérez et al, , 2014; those frequencies and the samples where they come from could be utilized as control groups that can be matched with other samples of patients with specific conditions such as Cleft lip and palate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 This bony arch is known as the PP 17 and is often bilateral 20 and can be divided into two types: partial (incomplete) and complete (Figure 2 and 3). 10,21 It was first reported by MacAlister 22 in 1893. Young et al 14 reported that putting a screw into PP during C1 lateral mass screw placement could cause injury to the vertebral artery.…”
Section: Anatomymentioning
confidence: 99%
“…The PP means "little posterior bridge" in Latin 3,6,[8][9][10][11][12][13][14][15][16][17][18] which describes an anomalous malformed bony bridge between the posterior portion of the superior articular process and the posterolateral portion of the superior margin of the posterior arch of the atlas. 9 The normal atlas ( Figure 1) is a ring-like structure consisting of two lateral masses connected by a short anterior arch and a longer posterior arch.…”
Section: Anatomymentioning
confidence: 99%